Possible role of bovine trophoblast giant cells in transplacental transmission of Neospora caninum in cattle. - Machado, Rosangela Z [UNESP]; Mineo, Tiago W P [UNESP]; Landim Jr., Lorivaldo P [UNESP]; Carvalho, Ana F [UNESP]; Gennari, Solange M [UNESP]; Miglino, Maria A [UNESP] (My University, 2007)
Neospora caninum is an aplicomplexan parasite that has brought several concerns to cattle raisers worldwide due to its relationship to fetal loss. However, the mechanism of the parasite's transplacental infection and induced abortions are not completely understood. Bovine trophoblastic binucleated cells (BNC) play a major role in the maternal-fetal interactions, migrating during the entire pregnancy from chorionic connections to uterine epithelium. This study aimed to investigate the possible role of BNC as phagocytic cells and its participation in the bovine transplacental infection of N. caninum. BNC was isolated by discontinuous Percoll gradient, and characterized by Hoeschst 33342 nucleus-specific staining. Isolated BNC were cultured in DMEM supplemented with 10% bovine fetal serum, and infected with 104 tachyzoites of N. caninum NC-1 strain. Parasite invasion was visualized by indirect immunofluorescence and Giemsa technique. Multiplication of parasites took place in 2-3 day cycles. Healthy cows' placenta and normal and infected cultured BNC was immunostained with monoclonal antibodies against CD-163, MAC-387 and iNOS, demonstrating their phagocyte capacity. Thus, BNC was characterized as cells with macrophagic activity, which may host N. caninum in vitro. Therefore, we may conclude that BNC could potentially participate in the transplacental infection of bovine neosporosis.